FUNCTIONAL EVALUATION OF THE POS-SURGICAL OF TEAR IN THE ROTATOR CUFF THROUGH THE SCALE OF THE UNIVERSITY OF CALIFORNIA, IN LOS ANGELES (UCLA) (Fiep Bulletin - online, 2014)
INTRODUCTION: The several alterations that occur on the shoulder and manifest  themselves with pain and limitation, are called Impact Syndrome. This syndrome presents multifactor etiology  and it can be divided according to its etiology into Secondary and primary impact.  The current treatments to patients with tear in the rotator cuff see the surgery and the physiotherapy  as important tools for checking the therapeutic results, because they try to minimize possible pos-treatment kinetic-functional disorders. GOAL : To evaluate the functionality of the shoulder in adult  individuals  submitted to surgical  treatment due to tears in the rotator cuff; METHODS :  It was used the functional scale of the University of Califórnia, Los Angeles (UCLA). The sample of this study was made up of 20 individuals of both genders, age between 29 to 73, submitted to surgical treatment, due to tears of the  rotator cuff with the same surgeon, using the mini-open repair and that had physiotherapeutic treatment in the year of 2005. RESULTS: The results found   point to high total levels of the scores where it was observed that 30% indicated good level and 45% excellent, totalizing 75%,. Relating to the satisfaction level, 85% of the sample indicated to be satisfied. CONCLUSION: The surgical treatment of the Rotator cuff, associated to the physiotherapeutic treatment using physical resources: Ultrasound scan, Short waves, TENS e  kinetic therapy   has good results and gets high level of satisfaction from patients after the rehabilitation.
Keywords: functionality; rotator cuff; surgical treatment; physiotherapeutic